1999
DOI: 10.1177/1358836x9900400406
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of treadmill testing in peripheral arterial disease: a comparison of a constant load with a graded load treadmill protocol

Abstract: This study aims to evaluate the reliability of repeated graded workload treadmill testing (G-test; 2 mph; 0% grade, increasing 2% every 2 min) and to compare the reliability of a constant workload treadmill protocol (C-test; 2 mph; 12% grade) versus the graded workload treadmill protocol in patients with intermittent claudication, studied longitudinally.A clinical trial investigating an orally stable prostacycline derivative that included 330 patients with intermittent claudication was performed. The trial emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Other studies have also confirmed better reproducibility with the graded compared with the constant-load test in PAD. 40 Importantly, in evaluations of patients with PAD, the high baseline reproducibility of the graded treadmill has been confirmed with the use of data from a multicenter trial. 41 The intrasubject coefficient of variation averaged 15% and was independent of the baseline exercise performance (the test was equally reproducible across the full range of baseline PWT values).…”
Section: Treadmill Reliabilitymentioning
confidence: 88%
“…Other studies have also confirmed better reproducibility with the graded compared with the constant-load test in PAD. 40 Importantly, in evaluations of patients with PAD, the high baseline reproducibility of the graded treadmill has been confirmed with the use of data from a multicenter trial. 41 The intrasubject coefficient of variation averaged 15% and was independent of the baseline exercise performance (the test was equally reproducible across the full range of baseline PWT values).…”
Section: Treadmill Reliabilitymentioning
confidence: 88%
“…To determine the initial and absolute claudication distances, patients walked on a treadmill at 0.67 m/s (1.5 mph) and 10% grade. 11 The first indication of claudication pain was recorded as initial claudication distance, and the total distance the patients could walk on the treadmill before stopping because of pain was the absolute claudication distance. 12 During the test, the technician asked the patient to confirm the presence or absence of pain to ensure the correct initial claudication distance was recorded.…”
Section: Quantitative Measuresmentioning
confidence: 99%
“…To determine reliability, four studies repeated one protocol. [42][43][44][45] The other four studies compared more treadmill protocols within the same group of patients. [46][47][48][49] Both C-and G-protocols were tested.…”
Section: Resultsmentioning
confidence: 99%